‘Time is of the essence’: upper-body aerobic exercise to improve cardiovascular health during inpatient rehabilitation within the first year following spinal cord injury – protocol for a randomised clinical trial - Samuel J E Lucas; Tom E Nightingale; Naveen Kumar; Shin-Yi Chiou; Afroditi Stathi; Manish Kalla; Daniel D Hodgkiss; Shane J T Balthazaar; Aheed E F Osman; Srinivasa C Budithi; Joy Roy Chowdhury (BMJ Open)
Introduction Individuals with spinal cord injury (SCI) face heightened cardiovascular disease (CVD) risks. While general exercise guidelines are promoted for SCI individuals, when and how to incorporate exercise during the subacute phase post-SCI remains unclear. Consequently, early aerobic exercise to reduce CVD risks is not standard practice in subacute SCI care, potentially missing an opportunity for optimal cardiovascular rehabilitation, especially given observed reductions in cardiac structure and function within the first year post-SCI. Addressing this gap could improve long-term cardiovascular health and health-related quality of life (HRQOL) for individuals with SCI. Early intervention might prevent worsening cardiovascular function and establish beneficial exercise habits. However, few studies have evaluated the effectiveness of early exercise interventions in this population. This study aims to provide insight into the impact of moderate-intensity arm-crank exercise training (ACET) on cardiometabolic, HRQOL, functional and fitness parameters in individuals with subacute (<12 months postinjury) SCI.Methods and analysis We will conduct a single-centre, two-group, single-blind randomised controlled trial with 42 participants who have sustained a cervical or thoracic SCI within the past year. The non-intervention group will receive hospital standard of care (control group) while the intervention group will receive hospital standard of care plus moderate-intensity ACET for 10 weeks in line with the SCI-specific exercise guidelines to improve cardiometabolic health. The primary outcome measure will be central arterial stiffness (carotid-to-femoral pulse wave velocity). Secondary outcomes include assessments of (1) blood biomarkers linked to CVD, (2) cardiac structure and function, (3) extracranial vasculature, (4) HRQOL, (5) cognitive function, (6) physical activity level, (7) cardiorespiratory fitness, (8) motor function and (9) feasibility outcomes. Assessments will occur at baseline (rehabilitation centre admission, −2 weeks), preintervention (0 weeks), postintervention (10 weeks) and follow-up (6 months after postintervention), for HRQOL outcomes only.Ethics and dissemination Ethical approval was obtained from the Wales Research Ethics Committee (HREC 22/WA/0329). Outcome data will be presented at international conferences, patient advocacy groups, health professional networks and community health events. Findings will be published in peer-reviewed journals and widely disseminated through strategic channels to reach researchers, healthcare providers, patients and the public.Trial registration number ISRCTN99941302.